Gender Differences in Psychological Impact of the Confinement During the COVID-19 Outbreak in Spain: A Longitudinal Study - Fenollar-Cortés, Javier; Jiménez, Óliver; Ruiz-García, Antonio; Resurrección, Davinia M. (Frontiers in Psychology, 2021)
The rapid spread of the coronavirus disease 2019 (COVID-19) has led the authorities to establish compulsory confinement for most of the Spanish population from March to May 2020. Severe isolation combined with the uncertainty and fear associated with the public health crisis can have a psychological impact on the general population. The aim of the current study was to compare possible gender differences in mental health and psychological measures throughout the confinement. One hundred and sixty-four Spanish participants (75% female; Mage = 39.8; SD = 13.5) completed the surveys at the beginning, middle, and end of the forced confinement. The psychological variables were associated with depressive, anxiety, stress, and intrusive/avoidance symptoms, as well as a total score for overall mental health, and a positive/negative affect measure. The results showed that although females had significantly higher scores than males in almost all measures at the beginning of the confinement, the gender differences were quickly vanishing away over time. In fact, intra-group analysis showed that while the female group significantly improved their results on most psychological measures, the male group improved on only one single measure. In summary, the results showed that although the female group started the confinement with higher levels of negative emotions (particularly symptoms of stress and avoidance) than the male group, these differences were significantly reduced in the first few weeks due to the overall improvement in the results of the female group.